A importância das fontes autotróficas campestres na teia trófica de passeriformes do interior de fragmentos florestais - Bertin, Edna Lais (Universidade do Vale do Rio dos Sinos, 2016)
Tropical forests are among the most important terrestrial habitats in terms of the concentration of biological diversity in the world (Ayres et al., 2005). These forests are home to more than 60% of all species already described, even though their extent is restricted to about 7% of the planet's area (Ewers et al. 2008; Gardner et al. 2009). Throughout its distribution, some of the largest formations of tropical forests are found in South America. Among them, the Atlantic Forest, the second largest tropical rainforest in extension in all of the Americas, stands out, second only to the Amazon Forest. Originally it covered more than 1.5 million km², covering northeastern Argentina, eastern Paraguay and Brazil. It is worth noting that Brazil alone is home to 92% of the entire area of ​​this Biome (Fundação SOS Mata Atlântica, 2011; Tabarelli et al., 2005), constituting an important region for its maintenance. Like most tropical forest formations, the Atlantic Forest has been suffering for centuries an intense process of area loss and fragmentation (Myers et al., 2000). Its current area is estimated to represent only 11.4% to 16% of its original extension (Ribeiro et al., 2009).
Keywords: Fontes autotróficas campestres; Isótopos estáveis; Fonte alóctone; Aves; Paisagens fragmentadas; Mata Atlântica; Country autotrophic sources; Stable isotopes; Allochthonous font; Birds; Fragmented landscapes; Atlantic Forest; ACCNPQ::Ciências Biológicas::Biologia Geral